TINJAUAN YURIDIS TERHADAP PEMBERIAN ASIMILASI KEPADA NARAPIDANA DALAM RANGKA PENCEGAHAN DAN PENANGGULANGAN PENYEBARAN COVID-19 DIKAITKAN DENGAN TEORI PEMIDANAAN - Putra, Kevin Maulana; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Since the existence of the assimilation program in the context of preventing and overcoming the spread of COVID-19, there are problems that need to be addressed, with the assimilation given whether the purpose of punishment, which is to provide a deterrent effect for perpetrators, has been fulfilled, whether it has guaranteed convicts who have received COVID-19 assimilation.. Recidivist or repetition of a criminal offense occurs in the event that a person commits a criminal act and has been sentenced to a criminal offense with a judge's decision who continues to commit another criminal act. In recidivists, it can be assumed that in the same way as the Realist discourse, a person commits more than one crime. Another factor that encourages recidivists is the ineffectiveness of the supervisory function by the Supervisory Agency (BAPAS).This research will be compiled using the juridical normative type of research, which is research that is focused on examining the application of the rules or norms in positive law. The approach used in this research is to use a normative approach, namely literature law research. This study examines the subject matter according to the scope and identification of problems through the statute approach (statue approach) is carried out by examining statutory regulations and regulations related to the legal issue under studyThe results of the research conducted by the author are, first to know the provision of assimilation to inmates in the context of preventing and overcoming the spread of COVID-19 based on the regulation of the minister of law and human rights number 10 of 2020 related to the theory of punishment, then the answer is how to achieve criminal responsibility for convicts who take recidivist action due to assimilation in the context of preventing and overcoming the spread of COVID-19 in Indonesian criminal law.Keywords: Assimilation Giving - COVID-19- Recidivist